CO2 reduction using nanomaterials as catalyst - Yee, Jiun Shyan (Nanyang Technological University, 2021)
The research for renewable energy has always been a top priority as fossil fuel is expected to deplete in the future. The conversion of carbon dioxide (CO2) into reusable clean energy had attracted the attention of many researchers owing to the immense potential of such technology that may one day be used to overcome the energy shortage and environmental crisis like global warming. CO2 can be collected from the environment and be converted into reusable fuel such as formic acid (HCOOH) through the electrochemical reduction reaction using Tin (Sn) based catalyst. However, such processes still suffer from major drawbacks like poor product selectivity and low current density which prevents adoption by the industries. Therefore, in this study, we proposed the use of Copper (Cu) doped Tin sulfide (SnS2) catalyst to address the drawbacks faced by traditional Sn catalyst. The new catalyst was synthesized through a hydrothermal process at 150 oC for 12 hours and placed onto carbon fiber papers which act as an electrode. Data obtained by this study showed promising results as the Cu-doped SnS2 catalyst had a much higher product selectivity towards HCOOH and a higher catalytic activity compared to the pristine SnS2 catalyst. This was because the doping process changes the catalyst’s electronic structure that favors the binding of *OCHO intermediates which are the precursor for HCOOH, while suppressing the unfavorable hydrogen evolution side reaction. In addition, the catalyst was able to maintain high stability with excellent faradaic efficiency throughout 40 hours of continuous operation and hence, these make Cu-doped SnS2 catalyst a potential candidate for large scale industrial applications.